400:5×[3+2-(60:2-10×3)+3]×2×1 cum rezolv
Răspunsuri la întrebare
Răspuns de
1
400:5×[3+2-(60:2-10×3)+3]×2×1=
400:5×[3+2-(30-30)+3]×2×1=
400:5×(3+2-0+3)×2×1=
400:5×2×2×1=
400:5×2×2=
80×4=320
Răspuns de
2
Răspuns:
1 280
Explicație pas cu pas:
400:5×[3+2-(60:2-10×3)+3]×2×1=
400:5×[3+2-(30-30)+3]×2×1=
400:5×(3+2-0+3)×2×1=
400:5×(5-0+3)×2×1=
400:5×(5+3)×2×1=
400:5×8×2×1=
80×8×2×1=
640×2×1=
1 280×1=
1 280
Alte întrebări interesante
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Biologie,
8 ani în urmă
Biologie,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă